Rumors ≠ Gossip - Julia Beaumont (Study and Scrutiny)
The purpose of this critical content analysis (CCA) is to inquire into how gossip is portrayed in young adult (YA) novels, drawing from the theoretical frameworks of critical feminist pedagogy (hooks, 1994; Webb et al., 2002) and culturally sustaining literacy pedagogy (Alim & Paris, 2017). Depictions of gossip and rumor-spreading in 10 YA texts were compared and analyzed using the methods of CCA (Johnson et al., 2016). Using critical feminist theoretical coding, the overarching themes illuminated that the action of rumor-spreading is often mislabeled as gossiping, and productive, positive gossip is often unnamed as such in YA literature.